Water balance studies of the Betwa basin - Sutcliffe, JV (MAUSAM, 1987)
A study of the Betwa basin, where a season of water surplus contrasts with a period of deficit, shows that annual soil moisture recharge may be estimated by comparing seasonal net rainfall with runoff. Detailed investigation of the Nion tributary shows that net rainfall is divided in sequence between soil moisture replenishment, groundwater recharge and runoff. A simple conceptual model reproduces reasonably not only the runoff but also the soil moisture and shallow groundwater storage.